If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2) = (2)(bt(1)) 2 = (2)(bt(1)) Reorder the terms for easier multiplication: 2 = 2(1bt) Remove parenthesis around (1bt) 2 = 2 * 1bt Multiply 2 * 1 2 = 2bt Solving 2 = 2bt Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2bt' to each side of the equation. 2 + -2bt = 2bt + -2bt Combine like terms: 2bt + -2bt = 0 2 + -2bt = 0 Add '-2' to each side of the equation. 2 + -2 + -2bt = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2bt = 0 + -2 -2bt = 0 + -2 Combine like terms: 0 + -2 = -2 -2bt = -2 Divide each side by '-2t'. b = t-1 Simplifying b = t-1
| 2x+24+4x-36+6x=180 | | 15x-15=113+x | | p=4x+15 | | J-17=(3) | | 3x-10=62 | | 3x-12=15x+24 | | K+20=0 | | 2(g+7)=20 | | 34=0.4(p+22) | | 5n+12+3n=2n+30 | | 12/2=x/15 | | D-3=(2) | | r^3+3r=5 | | 3x-12=15x+8 | | 7x+1.5x=32560 | | 27(n-1)=3(6) | | 3r+13r=-16 | | (x-8)2+(y+2)2=49 | | 27n-1=18 | | 2m-3n=2 | | M-4=(4) | | 4340+4125(215)=891215 | | 5k-14k+(10)=17 | | 4125+(215)=886,875 | | y^2+11y+118=0 | | 5+(10-1)(3)= | | 12b-11b=10 | | 4125(215)=886,875 | | 5a+2b=5 | | 5+(4-1)(3)= | | 7x+4-2x=10 | | 8x-(6x+8)=3x-41 |